Transparency and accountability - Pulverer, Bernd (WILEY-VCH Verlag, 2010)
EMBO Molecular Medicine is enriched by a number of innovative policies designed to enhance the editorial process: peer review process files, de-emphasis of confidential referee comments and cross-refereeing.